Exploring Progressive and Race-Conscious": An investigation into White Tufts University students' awareness of issues of race and racism - Chatillon-Reed, Anna H. (Tufts Archival Research Center, 2005)
This study investigates how White Tufts University students demonstrate awareness of issues of race and racism, an awareness that is prerequisite to (but by no means a guarantee of) further engagement with issues of race, racism, and White supremacy, and meaningful anti-racist thought and action. This awareness is manifested in three ways: using a vocabulary that opposes the dominant definitions about race and racism, engaging race and racial power as societally relevant, and acknowledging that all White people are implicated in the co-construction of White supremacy. There is little published research regarding how White undergraduate students are aware of, challenge, or interrupt White supremacy and racism; this study was conducted to help fill this gap. The data used in this analysis were collected through qualitative open-ended interviews with White undergraduate students in a variety of majors, and I utilize Critical Race Theory to frame an analysis of the resulting data themes. The data indicate that White Tufts students are more likely to demonstrate awareness of issues of race and racism if they have taken academic courses about structural inequalities based on gender or race.